DETERMINAN IMPULSIVE BUYING BEHAVIOR PEMBELIAN PRODUK FASHION MUSLIM PADA MARKETPLACE ERA NEW NORMAL DI MADIUN - Kasanah, Uswatun; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
This research conducted to see the effect of impulsive buying behavior factors on muslim female consumers in Madiun who purchase muslim fashion products online during the new normal period. The non-probability sampling technique used was purposive sampling and the population is muslim female consumers in Madiun, East Java and calculated using the unknown populations formula. The quantitative approach used in this research is based on primary data sources. Multiple linear regression analysis are used in hypothesis testing. Based on the research results, the consumer characteristics and situational factors has a significant positive effect, the website characteristics has a significant negative effect. The religiosity has no significant effect. The simultaneous test results showed a significant positive effect between consumer characteristics, website characteristics, situasional factors, and religiosity to impulsive buying behavior in purchasing muslim fashion products on the marketplace in the new normal.